Dynamic Alterations of the Gut Microbial Pyrimidine and Purine Metabolism in the Development of Liver Cirrhosis - Xiong, Yinghui; Wu, Li; Shao, Li; Wang, Yang; Huang, Zebing; Huang, Xun; Li, Chunhui; Wu, Anhua; Liu, Zhenguo; Fan, Xuegong; Zhou, Pengcheng (Frontiers in Molecular Biosciences, 2022)
Background: Liver cirrhosis is the common end-stage of liver diseases lacking effective treatment, thus studies for the prevention target is an urgent need. The intestinal microbiota (IM) play important roles for modulating liver diseases which were mediated by microbial metabolites. Despite decades of explosion microbial studies, the IM contribute to the development of cirrhosis and the intimate metabolic link remain obscure. Here, we aimed to reveal the dynamic alterations of microbial composition and metabolic signatures in carbon tetrachloride (CCl4)-induced liver cirrhosis mice. Methods: CCl4-treated mice or normal control (NC) were sacrificed (n=10 per group) after 5 and 15 weeks’ intervention. The disease severity was confirmed by Masson’s trichrome or Sirius red staining. Metagenomics sequencing and fecal untargeted metabolomics were performed to evaluate the composition and metabolic function of IM in parallel with the development of cirrhosis. Results: The CCl4-treated mice presented liver fibrosis at 5 weeks and liver cirrhosis at 15 weeks indicated by collagen deposition and pseudolobule formation, respectively. Mice with liver cirrhosis showed distinct microbial composition from NC, even in the earlier fibrosis stage. Importantly, both of the liver fibrosis and cirrhosis mice were characterized with the depletion of Deltaproteobacteria (P < 0.05) and enrichment of Akkermansia (P < 0.05). Furthermore, fecal metabolomics revealed distinguished metabolomics profiles of mice with liver fibrosis and cirrhosis from the NC. Notably, the pathway enrichment analysis pointed to remarkable disturbance of purine (P < 0.001 at 5 weeks, P = 0.034 at 15 weeks) and pyrimidine metabolic pathways (P = 0.005 at 5 weeks, P = 0.006 at 15 weeks) during the development of liver cirrhosis. Interestingly, the disorders of pyrimidine and purine metabolites like the known microbial metabolites thymidine and 2'-deoxyuridine were already occurred in liver fibrosis and continued in cirrhosis. Conclusion: These novel findings indicated the crucial role of IM-modulated pyrimidine and purine metabolites in the development of liver cirrhosis, which providing microbial targets for disease prevention.